SDN-Based Development Direction of C2 Network System According to Network Technology Development Trend - Lee, Gyu Min; Choi, Eun Ho; Cho, Bong Ik; Roh, Byeong Hee; Ryu, Dong Kuk; Park, Gyudong (Journal of Korean Institute of Communications and Information Sciences, 2020)
The advanced countries and the Korean military are making efforts to integrate the system by applying various network technologies centering on the command and control system, which is a key element of future war, in the rapidly changing war environment. Militarily advanced countries are actively using COTS and are actively adopting SDN technology that separates control and transmission for low cost, high efficiency and high survivability. In order to solve the problems of the command and communication system of the ROK military where flexibility and survivability are limited by separate system operation, this paper examines the current state of the introduction of the next-generation command and communication system and the development of transmission network technology in advanced countries and after reviewing the limitations of the current military structure, we propose the direction of development of command and communication systems to resolve the limitations.
Keywords: Command and Control System; Communication Network; Evolving Trend; Integrated Structure; SDN